FAKTOR KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA TERHADAP KELELAHAN PEKERJA - Ati Nurhayati; Nurul Hidayah; Pujiono Pujiono (Media Penelitian dan Pengembangan Kesehatan, 2025)
PT. X is a manufacturing industry located in Cimahi City. The working environment at PT. X has a fairly hot air temperature caused by the production process. Hot temperatures are one of the work environment factors that pose a risk to workers' health. Hot temperatures are one of the work environment factors that have a risk to the health of workers such as workers experiencing fatigue. The study aimed to determine the relation of individual characteristics and environmental factors on worker fatigue at PT.X. This research was analytical with cross-sectional design. While environmental factor variables consist of noise levels and lighting levels in the environment around workers during work. The sample wass PT.X workers in the production department as many as 32 people. Sampling was done by purposive sampling. Research data were obtained through interviews and measurements. Interviews were conducted to obtain individual characteristic data. Measurements were conducted to obtain data on the level of disturbance, level of disturbance, heat stress and worker fatigue variables.The results showed that out of 32 respondents, 17 people (53.1%) experienced fatigue. The results of the Chi-square test obtained a p-value of 0.014 on the heat stress variable indicating the influence of heat stress on worker fatigue at PT.X. Workers exposed to heat stress and experiencing fatigue were 14 people (73.3%). Worker fatigue affects productivity and if not immediately addressed can cause work accidents so that the company must pay more attention to the safety and health of its workers from exposure to environmental factors.